2012
DOI: 10.1103/physrevb.86.155133
|View full text |Cite
|
Sign up to set email alerts
|

Inverse transverse magneto-optical Kerr effect

Abstract: It is demonstrated that a static in-plane magnetic field is generated in a ferromagnetic film by ppolarised light obliquely incident on the film. This phenomenon can be called inverse transverse magnetooptical Kerr effect. The femtosecond laser pulse of peak intensity of 500 W/μm 2 generates in nickel an effective magnetic field of about 100 Oe. The value of the effective magnetic field can be increased by more than an order of magnitude at the surface plasmon polariton resonance excited in smooth metal dielec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 24 publications
0
35
0
1
Order By: Relevance
“…Finally, mention that Khanikaev et al [ 26 ] have also Figure 11. [173][174][175][176] The thickness providing maximum EM fi eld value for each material, and therefore optimum SPP excitation, are the ones used for the refl ectivity calculations in (a); (c) transversal MO Kerr effect, R pp , for a single Co fi lm and for Au/Co/Au trilayers (3 nm Au, d nm Co, 20 nm Au) as a function of the Co thickness; (d) R min for any combination of Au and Co thickness in the Au/Co/Au trilayers (3nmAu, dnmCo, dnmAu); (e) |H y | max for Au/Co/ Au trilayers as in (d); (f) R max for Au/Co/Au trilayers as in (d).…”
Section: Perforated Continuous Layers and Extraordinary Transmissiomentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, mention that Khanikaev et al [ 26 ] have also Figure 11. [173][174][175][176] The thickness providing maximum EM fi eld value for each material, and therefore optimum SPP excitation, are the ones used for the refl ectivity calculations in (a); (c) transversal MO Kerr effect, R pp , for a single Co fi lm and for Au/Co/Au trilayers (3 nm Au, d nm Co, 20 nm Au) as a function of the Co thickness; (d) R min for any combination of Au and Co thickness in the Au/Co/Au trilayers (3nmAu, dnmCo, dnmAu); (e) |H y | max for Au/Co/ Au trilayers as in (d); (f) R max for Au/Co/Au trilayers as in (d).…”
Section: Perforated Continuous Layers and Extraordinary Transmissiomentioning
confidence: 99%
“…[ 56,172 ] Some recent theoretical results show that the EM fi eld enhancement associated with plasmonic resonances could help increasing this effect. [173][174][175][176]…”
Section: Perforated Continuous Layers and Extraordinary Transmissiomentioning
confidence: 99%
“…Среди различных механизмов, позволяющих воздей-ствовать на состояние намагниченности образца [4][5][6][7][8][9], особое место занимает обратный эффект Фарадея. Дан-ный эффект заключается в намагничивании вещества при облучении его световой волной, обладающей кру-говой поляризацией.…”
Section: Introductionunclassified
“…These collective oscillations can be excited by incident light that matches its frequency and linear momentum. Furthermore, it has been broadly demonstrated that SPPs enhance the magneto‐optical activity of nano‐structured systems . This occurs even for those structures made of purely non‐ferromagnetic metals under small magnetic fields .…”
Section: Introductionmentioning
confidence: 99%